The effects of information systems resources on accounting information systems capabilities and co-operatives performance - Mohd Hadzrami, Harun Rasit (2020)
Accounting information system (AIS) usage is asserted as a contributing factor in improving the performance of business organizations. Indeed, AIS with sufficient capabilities can assist the management of an organization by providing useful and timely information for decision making. Previous literature revealed that studies examining the contributing factors of AIS capabilities are lacking. Therefore, based on the Resource-Based View (RBV) theory and resource complementarity perspectives, this study investigates the effects of information system (IS) resources on AIS capabilities and co-operative performance. For that purpose, seven categories of IS resources were proposed. Using a quantitative approach, questionnaires were used to collect data from 115 co-operative managers across Malaysia. Partial Least Square- Structural Equation Modelling was used to analyse the data. The study found that IS technical skills and planning and change management were significant factors that influence AIS capabilities. Using the resource complementarity argument, the study found that the combination of each IS resource has significant and positive effects on AIS capabilities. The study also found that AIS capabilities significantly influence cooperative’s performance. Furthermore, AIS capabilities were found to partially mediate the relationship between IS resources and co-operative’s performance. Theoretically, the study contributes to knowledge by providing an understanding of individual and complementary roles of IS resources in AIS capabilities building. Also, the study provides support for the importance of AIS capabilities and their mediating role in IS resources and performance relationship. Practically, the study provides guidelines for co-operatives’ stakeholders, particularly management, in planning and managing their IS resources. The checklist of IS resources proposed in this study could assist the management to identify the resources they are lacking and subsequently rectify the shortcoming. Also, this study emphasizes the importance of integrating and combining IS resources in building AIS capabilities and consequently improve cooperatives’ performance.